Zinc, Copper, Magnesium and Glycated Haemoglobin Levels in Obese Individuals - Ogbu , I. S. I. (New Advances in Medicine and Medical Science Vol. 4, 2023)
Background: Obesity is a key risk factor for a variety of serious disorders linked to micronutrient metabolism. Zinc, copper, and magnesium all play catalytic, structural, and regulatory roles in the body. Obesity may impair their bioavailability. Aim: It is critical to understand the state of these elements in obesity in order to recognize their involvement in obesity complications. Materials and Methods: The study included 86 obese people and 50 control persons. A fasting venous sample of 5ml was taken, with 3ml dispensed into a simple bottle and the remaining 2ml put into a lithium heparin container for glycated haemoglobin (HbA1c) measurement. The clotted sample was spun, and the serum was extracted for trace element analysis. HbA1c was calculated using the Karunamnayake and Chandrasekharan technique. The Mann and Yoe method was employed to estimate magnesium, whereas AAS was utilized to measure copper and zinc. Results: The mean zinc level of controls was higher than that of obese people (p = 0.017). The mean level of obesity in Class 111 was lower than in Class 1 but not in Class 11 (p = 0.05). Copper's value decreased in a non-significant way when BMI increased. Magnesium levels reduced (p = 0.043) as BMI increased. Similarly, as BMI increased, so did HbA1c concentration (p = 0.019). Conclusion: Obese people have zinc, copper, and magnesium deficiencies, indicating the necessity to evaluate trace element concentrations to prevent deficient states and accompanying health consequences.